Glutathione‐Responsive Nanoparticles of Camptothecin Prodrug for Cancer Therapy. Issue 3 (28th November 2022) - Zhang, Lingpu; Zhu, Lin; Tang, Lin; Xie, Jiayi; Gao, Yajuan; Yu, Changyuan; Shang, Kun; Han, Hongbin; Liu, Chaoyong; Lu, Yunfeng
Abstract: Camptothecin (CPT) is a potent chemotherapeutic agent for various cancers, but the broader application of CPT is still hindered by its poor bioavailability and systemic toxicity. Here, a prodrug that releases CPT in response to glutathione (GSH), which is commonly overexpressed by cancer cells is reported. Through assembling with PEGylated lipids, the prodrug is incorporated within as‐assembled nanoparticles, affording CPT with a prolonged half‐life in blood circulation, enhanced tumor targetingability, and improved therapeutic efficacy. Furthermore, such prodrug nanoparticles can also promote dendritic cell maturation and tumor infiltration of CD8 + T cells, providing a novel strategy to improve the therapeutic efficacy of CPT. Abstract : A camptothecin (CPT) prodrug is synthesized to assemble with PEGylated lipids as prodrug‐loaded nanoparticles, which can release CPT in response to overexpressed glutathione in cancer cells. Such prodrug nanoparticles endow CPT with a prolonged half‐life in the blood circulation and an enhanced immune response against cancer cells, resulting in significantly improved therapeutic efficacy.